Effect of cardiac resynchronisation therapy on occurrence of ventricular arrhythmia in patients with implantable cardioverter defibrillators undergoing upgrade to cardiac resynchronisation therapy devices. Issue 2 (29th August 2007) - Lin, G; Rea, R F; Hammill, S C; Hayes, D L; Brady, P A
Abstract : Background: Cardiac resynchronisation therapy (CRT) improves outcomes in selected patients with heart failure and left ventricular dysfunction. One mechanism of benefit is believed to be favourable ventricular remodelling. Whether CRT also decreases the frequency of ventricular arrhythmias and risk of sudden death is unknown. Objective: To determine the effect of CRT on frequency of ventricular arrhythmias and appropriate ICD therapies. Design: Retrospective cohort study. Setting: Single-centre, tertiary care facility (Mayo Clinic). Patients: 52 patients (46 male), aged 70 (SD 10) years, who underwent upgrade from an implantable cardioverter defibrillator (ICD) to a CRT-defibrillator were included. Interventions: Upgrade of ICD to CRT-defibrillator. Main Outcome Measures: Frequency of ventricular arrhythmias prior to and following upgrade to CRT device. Results: Ejection fraction increased from 22% (SD 8%) to 27% (SD 11%) following CRT. However, the frequency of non-sustained ventricular arrhythmias, sustained ventricular arrhythmias, and ventricular fibrillation was not significantly changed prior to and following CRT (2.38 (SD 9.78) vs 58.51 (SD 412.73) per patient per month, p = 0.66; 0.07 (SD 0.17) vs 0.16 (SD 0.52), p = 0.70; 0.05 (SD 0.12) vs 0.25 (SD 1.40), p = 0.12). Conclusions: CRT is not associated with a decrease in the frequency of ventricular arrhythmia or appropriate device therapy. Thus, use of CRT alone is not beneficial in decreasing the frequency of ventricular arrhythmias or the risk of appropriate ICD therapies.